The Role of Ground-Based Robotic Observatories in Satellite Projects - R. Hudec (Advances in Astronomy)
We discuss the role of robotic telescopes in satellite projects, as well as related strategies. Most satellite projects in space astrophysics focus on high-energy astrophysics from X-rays to gamma-rays. A large fraction of objects of high-energy astrophysics emit also optical light, which is, in many cases, variable. The observation of these sources at optical wavelengths can provide valuable inputs for multispectral analysis of various categories of celestial high-energy (HE) sources. As the magnitudes of numerous objects are bright and can be hence accessed by robotic ground-based observatories, these observations can contribute to investigations and analyses of HE sources. We discuss in detail this possible contribution, with emphasis on the ESA INTEGRAL mission. In addition to this, there are also satellite projects outside the high-energy astronomy, in which the robotic telescopes can also play an important role. We will illustrate this on the example of the ESA satellite Gaia. In this project, robotic telescopes are expected not only to verify the triggers detected by satellite (such as transients and flares) but also to provide additional (mostly photometric) data for better scientific cases.